Workshop and Certification of Oil and Gas Occupational Safety And Health Operators As An Implementation of Safety Culture Among High School Students In Dumai City - Budi Sulistiyo Nugroho; Farid Alfalaki Hamid Farid; Annasit Annasit; Astrie Kusuma Dewi; Susilo Handoko; Erdila Indriani; Hanifa Akrom; Sri Wahyu Warningsih; Diah Sekarwati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Oil and Gas Occupational Safety and Health (OSH) has strict requirements in its application to support the safety of workers, including standardisation of equipment, personnel, general oil and gas installation policies and work procedures so that oil and gas agencies or companies can operate reliably and safely. A small mistake or negligence is a failure to comply with safety requirements, which can be fatal and cause severe disasters to the company and the surrounding community. The main factor of work accidents that often occur is human or worker negligence or carelessness due to lack of knowledge. Dumai City became a 'pearl' on the East Coast of Sumatra and earned the nickname 'Oil City’ which produces various raw materials such as petroleum, natural gas, palm oil, and coconut oil; knowledge of OSH behaviour should be instilled from childhood so that the Workshop and Certification of Oil and Gas OSH Operators to SMA / K Students as the First Step in Implementing OHS Culture in the Dumai City School Environment to equip people with knowledge and expertise in the field of Oil and Gas OSH. Prevent work accidents and support and improve the K3 culture. The workshop was held from 1 to 5 March 2024, while the Oil and Gas OSH Certification exam for operator level was in collaboration with LSP PPSDM Migas for the STTK exam on 27-28 August 2024. Fifty participants attended the certification, and 31 participants were declared competent.